2018
DOI: 10.1016/j.asw.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the outcomes of two different approaches to CEFR-based rating of students’ writing performances across two European countries

Abstract: Comparing the outcomes of two different approaches to CEFR-based rating of students' writing performances across two European countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The authors claimed that even in a communicative teaching context, grammar and pronunciation should be emphasized to coordinate the development of subcomponents of oral proficiency. The research from HoIzknecht et al (2018) also showed that raters in Finland and Austria might differ in leniency; they agreed to a large extent on the CEFR levels of the participants if they are trained and experienced in the CEFR-based rubric.…”
Section: Synthesis and Findingsmentioning
confidence: 88%
See 2 more Smart Citations
“…The authors claimed that even in a communicative teaching context, grammar and pronunciation should be emphasized to coordinate the development of subcomponents of oral proficiency. The research from HoIzknecht et al (2018) also showed that raters in Finland and Austria might differ in leniency; they agreed to a large extent on the CEFR levels of the participants if they are trained and experienced in the CEFR-based rubric.…”
Section: Synthesis and Findingsmentioning
confidence: 88%
“…Slightly modified LPS can be a valid and reliable tool for assessing language proficiency. However, training LPS standards and the raters’ language proficiency levels should be reinforced (HoIzknecht et al, 2018; Silveira & Martins, 2020). Under these premises, using the LPS descriptors for rating can ideally lead to the same results across different contexts and achieve high congruence for all scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These categories explain the students' capability of mastering the target language. According to Holzknecht et al (2018), instead of using general classifications like "beginners," "intermediate," or "advanced" in the former KSSM assessment system, this proficiency scale offers a more accurate and dependable manner of gauging the students' mastery level in language learning. The new CEFR-aligned CBA emphasizes the peer and self-assessment to develop the independent language learner (Zhao & Zhao, 2020).…”
Section: The Inception Of Cefr Into Classroom Based Assessmentmentioning
confidence: 99%
“…For the identification of rater effects, we used the Many-Facets Rasch model (MFRM) (Linacre, 1994). For the sake of brevity, we will not present the relevant formulas, but more information about MFRM is available in Holzknecht et al (2018) and Lamprianou (2020). For the analysis of the data we used the Facets software (Linacre, 2005).…”
Section: Data Connectivity and Key Variablesmentioning
confidence: 99%